2014 Software Evolution Week - IEEE Conference on Software Maintenance, Reengineering, and Reverse Engineering (CSMR-WCRE) 2014
DOI: 10.1109/csmr-wcre.2014.6747191
|View full text |Cite
|
Sign up to set email alerts
|

Mining frequent bug-fix code changes

Abstract: Abstract-Detecting bugs as early as possible plays an important role in ensuring software quality before shipping. We argue that mining previous bug fixes can produce good knowledge about why bugs happen and how they are fixed.In this paper, we mine the change history of 717 open source projects to extract bug-fix patterns. We also manually inspect many of the bugs we found to get insights into the contexts and reasons behind those bugs. For instance, we found out that missing null checks and missing initializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
(12 reference statements)
3
17
0
Order By: Relevance
“…The answer implies that bug fixes affect fewer lines of code than tasks that implement new functionality. Osman et al have shown that, indeed, most bug fixes concern only one line of code [40]. It is intuitive that a single line of code change cannot cause as many review objections as the development of a full-blown new feature.…”
Section: Influences On the Number Of Changesmentioning
confidence: 99%
“…The answer implies that bug fixes affect fewer lines of code than tasks that implement new functionality. Osman et al have shown that, indeed, most bug fixes concern only one line of code [40]. It is intuitive that a single line of code change cannot cause as many review objections as the development of a full-blown new feature.…”
Section: Influences On the Number Of Changesmentioning
confidence: 99%
“…Missing null checks are the most recurrent bug pattern in Java systems [7]. This bug manifests itself as the Java NullPointerException.…”
Section: Motivationmentioning
confidence: 99%
“…For our experiment, we used the same software corpus from a previous study [7]. This corpus was built using a crawler that queries Github 2 for Java projects that have more than 5 stars (popular) and are more than 100KB in size (relatively large).…”
Section: A Experimental Corpusmentioning
confidence: 99%
See 2 more Smart Citations